Risk Factors Related to the Events of Leprosy in Children age 5-14 Years in City of Sorong West Papua (Medico Legal Update, 2020)
Leprosy is an infectious disease which is a national public health problem, because several regions in Indonesia have a high prevalence rate. There were 17,012 new cases of leprosy in Indonesia in 2010, consisting of 13,734 cases of Multi Basiler and 3,278 cases of PausiBasiler with a Newly Case Detection Rate (NCDR) of 7.22 per 100,000 population. The number was recorded as many as 20,329 cases with a prevalence of 0.86 per 10,000 population. In Indonesia, there are 12 provinces that still have leprosy rates above one person per 10,000 population, including the Province of Nangro Aceh Darussalam (1.51), South Kalimantan (1.07), East Java (1.67), North Sulawesi (2.57), Central Sulawesi (1.17), South Sulawesi (2.02), Southeast Sulawesi (1.21), Gorontalo (3.62), NTT (1.17), North Maluku (9.51), Maluku (3.47), and Papua (4.62). This study aims to see the risk factors for leprosy in children aged 5-14 years in Sorong City, West Papua Province. This type of research is a case control study and the population is children 5-14 years old in Sorong City with a sample of 54 respondents. The research data were analyzed using SPSS 16. Data analysis used the Chi-Square test. The results showed that the socioeconomic level p (0,000) 1 = risk risk) history of home contact p (0.000) 1 = risk risk) associated with the incidence of leprosy in children aged 5-14 years in Sorong City, while education p (0.569)> sig (0.05), parent’s occupation p (0.766)> sig (0, 05), personal hygiene p (0.136)> sig (0.05) is not a risk factor for the incidence of leprosy in children in Sorong City. It is recommended that parents increase knowledge about leprosy transmission by seeking information from both health workers and the mass media, as well as the public who can actively participate in supporting government programs and efforts to prevent leprosy.